Community health programmes for health promotion in rural community of Nepal - Rosyara, KP; Malla, B (Journal of Institute of Medicine Nepal, 2008)
Introduction: Community-based health programme is one of oldest multidisciplinary programme which effect lives of individuals in the community. These programmes in community settings are implemented to promote reproductive health, to prevent unintended pregnancy and to promote access to reproductive and preventive health services and beside that these programmes have been working to provide immunization vaccine, sexual transmission infections, community health education, community sanitarily systems, awareness regarding safe drinking water. Objectives: to identify the community health programmes which has been accessed in rural and peripheral residential area of Kirtipur Municipality Machhegaun, Kathmandu. Materials and Methods: An exploratory research design was followed with the help of semistructured questionnaire and information was obtained from the pre-selected area. A household survey was done by door-to-door visit. A total of eighty females were included in the study and the respondents attitude was studied. The study was conducted during the month of May to June 2007. The questionnaire was pre tested among ten females and their responses were not included in the final analysis. Results: Thirty seven females out of the eighty respondents were taken from nuclear family and rest forty three were from joint family. Further more in demographic variables showed most of respondents were in agriculture, which covers sixty five percentages. Other twenty five percentages were engaged in other fields, such as business, service daily wages etc. Hundred percentages of the respondents were covered by vaccines and fifty percentages females used permanent family planning and only 21.25 percentages used temporary family planning tools. But 28.75 percentages women did not use family planning tools. Majority of females got their first child between the age 20 to 39 year and rest 18.75 percentages got below 20 years and 25 percentages got above 40 years. Conclusion: The respondents opinion was positive and, community health programmes were playing vital role in the community to promote health status of the people. The respondents felt that there was an unfair advantage of community health programmes lunched in the area and Government, non government health institute and private medical service providers were playing leading role to change people to healthy behavior. Keywords: Community health, health promotion, healthy behavior, community people The full text of this paper is available at Journal of Institute of Medicine website